Justice League : the world's greatest superheroes - Dini, Paul (DC Comics, 2024)
"DC Comics proudly presents the acclaimed run on Justice League from the Eisner Award-winning team of artist Alex Ross and writer Paul Dini! Between 1998 and 2003, Dini, the Emmy Award-winning producer of Batman Beyond and The New Batman/Superman Adventures, joined forces with the incomparable Ross to create six oversize tabloid editions of stories featuring the World’s Greatest Super Heroes. These classic works for all ages feature the iconic DC characters in a unique storytelling format that combines aspects of both comics and picture books. Also included are several pages of promotional art, preliminary art and thumbnails, art done for DC Direct product, model-to-finished-painting comparisons, reflections by the book’s creators and much more! This landmark volume also features an introduction by award-winning book designer and author Chip Kidd, and an eight-page foldout featuring an image of every JLA member by Ross."--Publisher.